(untitled) (The Geographic Base, 2023)
Nepal, characterized by diverse and rugged topography, is prone to landslides due to various natural factors such as heavy rainfall during monsoons, frequent seismic activity, steep slopes, and adverse geological conditions. The situation worsens during the monsoon period, posing long-term threats to individuals and residential properties. The study aims to determine the landslide controlling factors in Siddhababa and Shrawan Danda, located north of Butwal City. Geologically, the region lies in the Sub-Himalaya or Siwalik region of Nepal. Field conditions were evaluated at and around the landslide regions in this research from the perspective of engineering geology, tectonics, and other man-made interventions. The study’s main objective was to determine the geological cause of landslides in this region. Inherently weak geological settings of rocks and active tectonics of the region are the major causes of landslides in these areas. The most remarkable is that the Himalayan Frontal Thrust (HFT), an active fault of the Himalayas, passes from this area. Additionally, the alternating layers of sandstone and mudstone, the hard and soft rock orientation, contrasting rates of weathering and densely developed adverse discontinuities are the other factors contributing to landslides in these areas. Along the Siddhartha Highway in the Siddhababa area, rockfall incidents have resulted in significant loss of life and property. Similarly, the Shrawan Danda landslide has caused extensive damage to infrastructures and livestock in the densely populated settlement at its base due to debris flow in the past.